Analisis Perlindungan Hukum Terhadap Anak Sebagai Korban Kejahatan Kekerasan Seksual - Dimas Handoko; Yeni Widowaty (Media of Law and Sharia, 2022)
Children are a gift from God that must be looked after as well as possible. Children are the hope of every family as the next generation of nation and civilization. As the next generation of the nation, children must grow and develop optimally in all aspects of their development, both physically and psychologically. To achieve optimal child development, of course, children must receive protection from all forms of violence against children. With the formulation of the existing problems, namely the factors that cause sexual violence crimes and forms of legal protection for children as victims of sexual violence crimes. This research is a normative juridical law research by analyzing court decisions. This research relies heavily on Primary and Secondary data sources. The results of this study are factors that make perpetrators commit crimes of sexual violence against children, namely lack of supervision from parents, being influenced by the environment, impulsive behavior and low self-control, lack of instilling morals and values from the family, lack of closeness to family and forms of protection The legal results of this research are Providing legal assistance to children to fulfill children's rights as victims of sexual violence against children, Providing protection and assistance to children as victims of sexual violence crimes while undergoing the legal process until a decision is obtained in court, Seeking a sanction that will be given to the accused objectively in order to fulfill a justice.